Epicardial pacemaker as a bridge for pacemaker-dependent patients undergoing explantation of infected cardiac implantable electronic devices - Maisary, Sameer al-; Romano, Gabriele; Karck, Matthias; De Simone, Raffaele (Journal of cardiac surgery, 2019)
Background and aim of the study Cardiac implantable electronic device (CIED) implantation is associated with an increase in CIED infection. For pacemaker-dependent patients, temporary pacemaker leads are implanted until infection remission, which allows new CIED implantation. We compared the outcome of pacemaker-dependent patients with infected CIED based on whether a combined single procedure of epicardial pacemaker implantation with system extraction or a temporary transjugular pacemaker implantation with interval system implantation was performed. Methods This retrospective study included pacemaker-dependent patients with CIED infection who were divided into two groups: the Tempo and Epi groups. The Tempo group received temporary transvenous pacemaker connected to an external pulse generator. After infection remission, a new permanent pacemaker was implanted, and the temporary pacemaker leads were removed. The Epi group received implantable epicardial right-ventricular pacemaker through infrasternal inferior pericardiotomy, and a permanent pulse generator was implanted through the same incision between the subcutaneous tissue and abdominal fascia. Results Sixty-six patients were included. Forty-two patients with epicardial pacemakers were discharged after 9.5 ± 8.8 days without infection of the newly implanted epicardial pacemaker. Patients with temporary transjugular pacemaker lead were discharged 23 ± 15 days after receiving permanent pacemakers. No serious complications were recorded in the Epi group. Conclusions CIED infections in pacemaker-dependent patients can be treated through epicardial pacemaker implantation that allows early patient mobility and reduces hospital stay with no risk of epicardial pacemaker infection. Epicardial pacemakers can be used as a bridge until permanent intravenous CIED is implanted or as a replacement for permeant intravenous CIED.